Biological soil crusts of cold deserts of W Himalaya - Čapková, Kateřina (Jihočeská univerzita, 2016)
Proposed thesis is focused on the role of soil microbial crusts in the extreme environmental conditions of high-elevation cold desert of W Himalaya. Despite the importance of microbial soil crusts in arid soils, the biodiversity of their microbial communities, their role and function are still unclear. Our knowledge about functioning of these outlying ecosystems in this part of the world is still very insufficient in general. The area of Ladakh is perfect place for studying the microbial soil crust arid climate and extreme elevation aroud 6000 m a.s.l. represents unique condition for well-developed soil crusts communities. The whole region is unaffected by human activities or plant invasions, so we can study soil crusts in pristine natural condition. Our investigations is focused on soil microbial community of BSCc in Ladakh region. It combines range of aspects connected with BSCs such as taxonomical composition, changes of diversity and activity in relation to environmental condition. The thesis is the first compilation of studies concerned on microbial communities in area of Ladakh and one of the first work investigating the ecophysiology of BCSs in cold desert.
Biological soil crusts of cold deserts of W Himalaya
Keywords: soil crusts; cold deserts; high mountains; soil microbiology